On the Role of Calcium-Permeable AMPARs in Long-Term Potentiation and Synaptic Tagging in the Rodent Hippocampus - Park, Pojeong; Kang, Heather; Sanderson, Thomas M.; Bortolotto, Zuner A.; Georgiou, John; Zhuo, Min; Kaang, Bong-Kiun; Collingridge, Graham L. (Frontiers in Synaptic Neuroscience, 2019)
Long-term potentiation (LTP) at hippocampal CA1 synapses is classically triggered by the synaptic activation of NMDA receptors (NMDARs). More recently, it has been shown that calcium-permeable (CP) AMPARs can also trigger synaptic plasticity at these synapses. More specifically, their activation is required for the PKA and protein synthesis dependent component of LTP that is typically induced by spaced stimulation protocols. Here we present new data that build upon these ideas, including the requirement for synaptic activation and NMDAR dependence. We also present data that implicate CP-AMPARs in synaptic tagging and capture, a fundamental process that is important for the input-specificity of protein synthesis dependent LTP.